Sistem Pendukung Keputusan Pemilihan Alat Kesehatan pada Poli Gigi Menggunakan Metode Fuzzy Mamdani (Studi Kasus: Klinik Pratama Wiwit) - Safitri, Eli; Wijaya, Dhina Puspasari; Pramuntadi, Andri; Gutama, Deden Hardan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Dental equipment plays a crucial role in supporting the quality of service at the Dental Clinic. At the Pratama Wiwit Clinic, equipment selection is still done manually without systematic analysis, making it prone to procurement errors and budget waste. The main research question is how the Mamdani Fuzzy Method can help determine the best dental equipment based on criteria such as price, brand, warranty, supplier, and equipment degradation. The research method includes data collection through observation, interviews, and documentation, followed by fuzzification, rule formation, fuzzy inference, and defuzzification. Test results show the system provides accurate recommendations with the highest fuzzy value of 0.85 for a device prioritized for procurement. This system has been proven to improve the objectivity and efficiency of the procurement process and can be adopted by other dental clinics to minimize waste and ensure the availability of equipment as needed.